Doripenem Dosing Recommendations for Critically Ill Patients Receiving Continuous Renal Replacement Therapy - Samtani, Mahesh N. (International Scholarly Research Network, 2012)
Doripenem dosing regimens for patients receiving continuous venovenous hemofiltration (CVVH) and continuous venovenous hemodiafiltration (CVVHDF) were devised based on an established efficacy criterion (free plasma doripenem concentrations above the minimum inhibitory concentration [fT > MIC] of 1 mg/L for ≥35% of the dosing interval) while maintaining exposure below that with the highest studied dose of 1000 mg infused over 1 hour every 8 hours in healthy subjects. Simulations were utilized to assure ≥90% probability of achieving the efficacy criterion with the recommended doripenem regimens. Inflated intersubject variability of 40% (coefficient of variation) was used for pharmacokinetic parameters (representative of clinical variation) and nonrenal clearance was doubled to account for potential changes with acute renal insufficiency. Results indicate that a reduction in doripenem dose will be needed for critically ill patients receiving CVVH or CVVHDF. This work was conducted to fulfill a health authority request and resulted in the addition of dosing recommendations to the Doribax Summary of Product Characteristics.